Managerial Overconfidence, Inflation Uncertainty, And Capital Structure Choice: Evidence Of Malaysian Shari'ah-Compliant Firms - Osman, Khairul Nizam (2023)
Using a unique dataset of 332 manufacturing and non-manufacturing Malaysian Shari'ah public-listed firms over the 2010-2018 period, this thesis explores capital structure choice in the context of managerial overconfidence and inflation uncertainty, focusing on the dynamic interaction between the two. The main empirical findings of a panel robust two-step System GMM show that increased managerial overconfidence, proxied by the Malaysian Institute of Economic Research’s (MIER) Business Condition Index (BCI), increases financial leverage in manufacturing firms of considerable size, aligning with the overconfident-standard pecking order theory proposed by Heaton (2002). The study also revealed that both measures of inflation uncertainty, namely variability and uncertainty, exert a direct negative influence on the capital structure of Shari’ah firms, albeit in distinct ways